Effect of reflective thinking on academic performance among undergraduate dental students - Suraj Reddy Loka; Dolar Doshi; Suhas Kulkarni; Pavan Baldava; Srilatha Adepu (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Self-directed learning is a vital principle promoted in health profession's education, particularly with the increasing use of online learning methods. Likewise, reflection has been recognized as an indispensable and formidable concept for learning which plays a positive role in fostering students' self-reflection, critical thinking, and development of professional values and skill. Hence, the present study was undertaken to identify the effect of reflective thinking on academic performance among undergraduate dental students. MATERIALS AND METHODS: Reflective thinking was assessed among 2nd-, 3rd-, and 4th-year undergraduate dental students and interns of a dental college and hospital in Hyderabad. Reflection questionnaire assessed habitual action, understanding, reflection, and critical reflection on a 5-point Likert scale. The percentage of marks obtained in the last university examinations was considered for academic performance. The completed questionnaires were analyzed using the Statistical Package for the Social Sciences software (SPSS version 20).P < 0.05 was considered statistically significant. RESULTS: A total sample of 263 individuals comprising 188 (71.5%) females and 75 (28.5%) males participated in the study. Our findings showed that the four scales of reflective thinking, such as habitual action (P = 0.0001*), understanding (P = 0.02*), reflection (P = 0.02*), and critical reflection (P = 0.01*), showed statistically significant difference based on the year of study. However, no difference based on gender was noted. Reflection (17.2 ± 2.41) and critical reflection (16.3 ± 2.77) mean scores were highest among 4th years. Higher understanding (17.83 ± 1.78) and reflection (17.33 ± 2.01) mean scores were observed among students who attained more than 75% in their academic performance. CONCLUSION: Thus, the present study emphasizes the role of reflective thinking and its significance in academic learning process.